2020
DOI: 10.1088/1367-2630/abc1fa
|View full text |Cite
|
Sign up to set email alerts
|

High-density electron–ion bunch formation and multi-GeV positron production via radiative trapping in extreme-intensity laser–plasma interactions

Abstract: Multi-petawatt laser systems will open up a novel interaction regime mixing collective plasma and quantum electrodynamic processes, giving rise to prolific generation of gamma-ray photons and electron–positron pairs. Here, using particle-in-cell simulations, we investigate the physics of the interaction of a 1024 W cm−2 intensity, 30 fs duration, circularly polarized laser pulse with a long deuterium plasma at classically overcritical electron density (1022 cm−3). We show that radiative trapping of the plasma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…This regime differs significantly from the quasi one-dimensional hole boring or light sail regimes which occur at higher densities, and where QED processes have been studied recently [15,17]. The previous simulations of the channelling regime performed for a 0 10 3 revealed that the laser pulse can trap plasma electron which field drags ions, hence dense electron-ion bunch is formed right in the laser pulse [19,20,21]. Radiation reaction plays a crucial role in this electron trapping and plasma transparency [20,21], however, the laser pulse still can travel a long distance despite of the electron trapping and "snow plough" effects.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…This regime differs significantly from the quasi one-dimensional hole boring or light sail regimes which occur at higher densities, and where QED processes have been studied recently [15,17]. The previous simulations of the channelling regime performed for a 0 10 3 revealed that the laser pulse can trap plasma electron which field drags ions, hence dense electron-ion bunch is formed right in the laser pulse [19,20,21]. Radiation reaction plays a crucial role in this electron trapping and plasma transparency [20,21], however, the laser pulse still can travel a long distance despite of the electron trapping and "snow plough" effects.…”
Section: Introductionmentioning
confidence: 89%
“…The previous simulations of the channelling regime performed for a 0 10 3 revealed that the laser pulse can trap plasma electron which field drags ions, hence dense electron-ion bunch is formed right in the laser pulse [19,20,21]. Radiation reaction plays a crucial role in this electron trapping and plasma transparency [20,21], however, the laser pulse still can travel a long distance despite of the electron trapping and "snow plough" effects. Also, pair photoproduction for such field strength lead to a small number of positrons whose field is not enough to influence the laser pulse propagation.…”
Section: Introductionmentioning
confidence: 99%
“…The most important effects are high-frequency radiation emission by electrons pushed in the laser-field (with a consequent back reaction on individual electrons, the radiation reaction (RR)) and the multi-photon Breit-Wheeler (BW) process leading to the generation of electron-positron pairs [37] . These QED effects, usually expected to deplete energy from a physical system [38][39][40][41][42] , may though significantly modify the collective plasma dynamics [43] with yet unexplored indirect effects on the ion energy.…”
Section: Introductionmentioning
confidence: 99%
“…Tremendous effects have been made to understand the QED plasma dynamics [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] and to explore possibilities of their preparation in laboratories [48][49][50][51][52][53][54][55][56][57][58][59][60] . The QED plasma dynamics 9,[60][61][62] is characterized by strong field QED and collective plasma effects.…”
Section: Introductionmentioning
confidence: 99%